2021
DOI: 10.1136/bcr-2021-241893
|View full text |Cite
|
Sign up to set email alerts
|

Otoneurological presentations of COVID-19

Abstract: COVID-19 usually begins with respiratory symptoms but may also cause neurological disturbances by direct (viral invasion) or indirect (immune-mediated) mechanism. Common neurological injury described in the literature include infectious toxic encephalopathy, viral encephalitis and Guillain-Barré syndrome. We present two cases diagnosed with COVID-19 who presented with isolated neurological deficit along facial nerve and vestibular nerve. Both recovered with medical management and rehabilitative exercises. Isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Tools had 8 items for case reports and 10 for case series. Included case reports ( n = 39) had a mean score of 6.385 ± 1.41 with scores ranging from 2 to 8 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 10 case series had a mean score of 5.60 ± 2.01, and scores ranged from 3 to 9. 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 The detailed results of the quality assessment are provided in Supporting Information: File S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tools had 8 items for case reports and 10 for case series. Included case reports ( n = 39) had a mean score of 6.385 ± 1.41 with scores ranging from 2 to 8 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 10 case series had a mean score of 5.60 ± 2.01, and scores ranged from 3 to 9. 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 The detailed results of the quality assessment are provided in Supporting Information: File S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Tools had 8 items for case reports and 10 for case series. Included case reports ( n = 39) had a mean score of 6.385 ± 1.41 with scores ranging from 2 to 8 12–50 10 case series had a mean score of 5.60 ± 2.01, and scores ranged from 3 to 9 51–59 . The detailed results of the quality assessment are provided in Supporting Information: File .…”
Section: Methodsmentioning
confidence: 99%
“…In this review, we have found eighteen papers reporting some diagnosed vestibular dysfunction (Table 1). The primary pathology described within the reports has been BPPV [Abdelrahman and Shafik, 2021;Maslovara and Košec, 2021;Picciotti et al, 2021;Cetin, 2022] and vestibular neuronitis [Malayala and Raza, 2020;Vanaparthy et al, 2020;Aasfara et al, 2021;Giannantonio et al, 2021;Shinde et al, 2021;Mat et al, 2023]. Some cases of labyrinthitis [Gerstacker et al, 2021;Perret et al, 2021], acute vestibular syndrome [Zaffina et al, 2021], and 1 case of acute bilateral vestibulopathy have also been reported [Lee et al, 2022].…”
Section: Otoneurological Findings In Sars-cov-2 Patientsmentioning
confidence: 99%